Knowledge, attitudes, and practices of mothers on exclusive breastfeeding during the first six months in Da Nang - Thuy, Nguyen Thi; Cuc, Nguyen Thi Kim; Thuy, Huynh Thi My (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Exclusive breastfeeding (EBF) for the first six months of life is strongly recommended by the World Health Organization and UNICEF as the optimal method of infant feeding. Despite its well-documented benefits, EBF rates in Viet Nam remain suboptimal. This study aimed to assess knowledge, attitudes, and practices (KAP) regarding EBF and to identify associated factors. Methods: A cross-sectional study was conducted from March to April 2025 at three randomly selected health stations in Da Nang City. A total of 350 mothers were recruited using simple random sampling. Data were collected through a structured questionnaire adapted from validated tools, covering sociodemographic characteristics, knowledge (10 items), attitudes (5 items), and practices (3 items). Cronbach's alpha coefficients were 0.82, 0.83, and 0.81, respectively. Data were analysed using SPSS 26.0 with descriptive statistics and chi-square tests. Results: Most mothers (98.0%) demonstrated good knowledge, and 95.4% showed positive attitudes towards EBF; 88.3% maintained exclusive breastfeeding for six months. Maternal education level was significantly associated with breastfeeding practice (p = 0.030), while parity was related to attitudes (p = 0.030). Conclusion: The majority of mothers in Da Nang had good knowledge, positive attitudes, and appropriate practices regarding EBF. However, a small proportion still demonstrated suboptimal practices.